Sleep quality and clinical rotations: unveiling the impact on final‑year nursing students - Mohamed Ariffin, Suzilawati; Sahar, Muhammad Faroq; Muhamad, Suhana (Penerbit Universiti Sultan Zainal Abidin, 2025)
Sleep disturbances are common among students and may be exacerbated by shift work. Nursing students encounter shift patterns during clinical rotations, which can affect sleep quality. This study evaluated sleep quality among fourth year nursing students at IIUM Kuantan, described the intensity of their clinical rotations and examined the association between rotation intensity and sleep quality. This descriptive cross sectional study was conducted among 136 fourth year nursing students at IIUM Kuantan. Data were collected using the Pittsburgh Sleep Quality Index (PSQI) and a validated questionnaire measuring clinical rotation intensity. Analyses were performed using SPSS; Fisher's exact test was used to examine the association between sleep quality and clinical rotation intensity. A p value < 0.05 was considered statistically significant. Of the 136 participants, 33 (24.3%) reported good sleep quality and 103 (75.7%) reported poor sleep quality. Clinical rotation intensity was reported as low by 1 participant (0.7%), moderate by 93 participants (68.4%) and high by 42 participants (30.9%). Fisher's exact test indicated no significant association between sleep quality and clinical rotation intensity (p = 0.559). In conclusion, poor sleep quality was common among the participating nursing students but was not significantly associated with clinical rotation intensity in this sample. Further studies with larger, multi centre samples and objective sleep measures are recommended to explore this relationship more comprehensively.